Children with problem drinking parents in Sweden: Prevalence and risk of adverse consequences in a national cohort born in 2001. (11th November 2021) - Ramstedt, Mats; Raninen, Jonas; Larm, Peter; Livingston, Michael
Abstract: Introduction: To estimate the prevalence of children with problem drinking parents in Sweden and the extent to which they have an elevated risk of poor health, social relationships and school situation in comparison with other children. Methods: Survey with a nationally representative sample of Swedish youth aged 15–16 years ( n = 5576) was conducted in 2017. A short version of The Children of Alcoholics Screening Test (CAST‐6) was used to identify children with problem drinking parents. Health status, social relations and school situation were measured by well‐established measures. Overall prevalences for girls and boys were presented as well as relative risks (RR) of harm for children with problem drinking parents compared with other children. Results: A total of 13.1% of the sample had at least one problem drinking parent during adolescence according to CAST‐6—a higher proportion of girls (15.4%) than boys (10.8%). This group had an elevated risk of poor general health as well psychosomatic problems compared with other children (RR 1.2–1.9). They were also more likely to use medication for depression, sleeping difficulties and anxiety (RR 2.2–2.6). Their social relations were also worse especially with their father (RR 3.1) and they had more problems at school (RR 2.6). Discussion and Conclusions: The risk of problems related to parental drinking goes beyond the most severe cases where parents have been in treatment for their alcohol problem. This is important knowledge since the majority of problem drinkers never seek treatment and the major part of parental problem drinking is found in population samples.